Relationship between movement dysfunctions and sports injuries according to gender of youth soccer player - Lim, K.-H.; Seo, T.-B.; Kim, Y.-P. (Journal of Exercise Rehabilitation, 2020)
The purpose of this study is to investigate relationship between movement dysfunctions and sports injuries according to gender of youth soccer player. Thirty-eight middle school soccer players participated in this study and they were divided into male (n=19) and female (n=19) groups. The Functional Movement Screen (FMS) and the Quadriceps-angle (Q-angle) during single-leg squat were analyzed for identifying imbalance and asymmetry of the body, and sports injury questionnaire was examined for 6 months after FMS test. The number of sports injuries did not show significant difference between youth male and female soccer athletes. In FMS results, the scores of overhead squat, hurdle step, in-line lunge, shoulder mobility, active straight leg raise, and rotary stability and the total scores were no significant differences between gender, but the score for the trunk stability push-up was significantly higher in male group than female group. There was no significant difference of Q-angle values between the left and right legs, but Q-angle value between youth male and female groups significantly showed interaction. Therefore, the present data suggested that FMS and Q-angle during single-leg squat might be indicators to predict and/or prevent sports injury in youth male and female soccer players.